2008
DOI: 10.1590/s1517-86922008000100005
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho da força em idosas após duas intensidades do exercício aeróbio

Abstract: RESUMO O objetivo do presente estudo foi comparar a influência aguda de duas intensidades de característica aeróbia, sobre o número de repetições numa sessão de treinamento de força (TF) em idosas fisicamente ativas. Oito volun-tárias (67,5 ± 4,8 anos; 58,6 ± 2,2 kg; 156 ± 5,9 cm) com experiência em ambas atividades, realizaram 20 minutos de caminhada em esteira rolante com intensidades pré-determinadas (60 ou 80% da FC máx.) e imediatamente após, realizaram uma sessão de TF nos exercícios de pressão de pernas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
2
1
4
Order By: Relevance
“…In contrast, in 2008 Lemos et al reported impaired muscle strength gain after performing aerobic exercises at different intensities prior to muscle-strengthening exercises [28]. Although a direct measure of muscle strength was not used, the results presented herein challenge data presented earlier.…”
Section: Discussioncontrasting
confidence: 67%
“…In contrast, in 2008 Lemos et al reported impaired muscle strength gain after performing aerobic exercises at different intensities prior to muscle-strengthening exercises [28]. Although a direct measure of muscle strength was not used, the results presented herein challenge data presented earlier.…”
Section: Discussioncontrasting
confidence: 67%
“…It is a consensus that a greater number of repetitions of the exercise can be a trigger mechanism of fatigue that can interfere with the gain in muscle strength. Likewise, the use of heavy weights can contribute to a greater accumulation of metabolites and a depletion of energy substrates 38 . In this study, the percentage of repetition maximum (75% 1RM), the number of sets (three for each exercise) and the number of repetitions (eight in each serie) were used.…”
Section: Discussionmentioning
confidence: 99%
“…Recomenda-se inspirar antes de levantar a carga e expirar durante a contração, evitando a manobra de Valsalva. 32,33 No entanto, esses estudos devem ser comparados ao presente estudo com cautela, pois foram realizados em idosos, mas sem a caracterização da SI. Na literatura há escassez de estudos relacionados ao fortalecimento para idosos com SI.…”
Section: Discussionunclassified